2019
DOI: 10.1111/febs.15106
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible versus repairable membrane poration: differences in permeabilization elicited by Bordetella Adenylate Cyclase Toxin and its hemolysin domain in macrophages

Abstract: Rapid plasma membrane repair in response to pore-forming toxins is crucial for cell survival, but the molecular mechanisms employed by eukaryotic nucleated cells to maintain membrane integrity and the specificities of such pathways remain poorly understood. Here, we have explored the permeabilization elicited by the Bordetella pertussis adenylate cyclase toxin, a 200-kDa protein toxin with a-helical pore-forming domain that forms pores of tunable size, and evaluated the response of target macrophages to such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Recently, we explored the permeabilization elicited by sublytic doses of ACT on target macrophages and evaluated whether the permeabilized cell membrane was resealed or not, and we found that the full-length toxin induces an irreversible membrane permeabilization that eventually leads to cell death [ 84 ] (Etxaniz et al, manuscript in revision), which suggests that cellular repair mechanisms are not operative in the ACT-treated macrophages. Interestingly, an ACT mutant extending from amino acids 483 to 1706 (ACT-∆N482 hemolysin), which contains the entire ACT RTX hemolysin domain, induces by contrast a transient membrane permeabilization that is rapidly reverted in a time scale of minutes (≈30 min) by a repair pathway activated by extracellular Ca 2+ influx and that requires ATP [ 84 ] (Etxaniz et al, manuscript in revision).…”
Section: Act Toxin: An Adenylate Cyclase Enzyme Fused To An Rtx Hementioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we explored the permeabilization elicited by sublytic doses of ACT on target macrophages and evaluated whether the permeabilized cell membrane was resealed or not, and we found that the full-length toxin induces an irreversible membrane permeabilization that eventually leads to cell death [ 84 ] (Etxaniz et al, manuscript in revision), which suggests that cellular repair mechanisms are not operative in the ACT-treated macrophages. Interestingly, an ACT mutant extending from amino acids 483 to 1706 (ACT-∆N482 hemolysin), which contains the entire ACT RTX hemolysin domain, induces by contrast a transient membrane permeabilization that is rapidly reverted in a time scale of minutes (≈30 min) by a repair pathway activated by extracellular Ca 2+ influx and that requires ATP [ 84 ] (Etxaniz et al, manuscript in revision).…”
Section: Act Toxin: An Adenylate Cyclase Enzyme Fused To An Rtx Hementioning
confidence: 99%
“…Recently, we explored the permeabilization elicited by sublytic doses of ACT on target macrophages and evaluated whether the permeabilized cell membrane was resealed or not, and we found that the full-length toxin induces an irreversible membrane permeabilization that eventually leads to cell death [ 84 ] (Etxaniz et al, manuscript in revision), which suggests that cellular repair mechanisms are not operative in the ACT-treated macrophages. Interestingly, an ACT mutant extending from amino acids 483 to 1706 (ACT-∆N482 hemolysin), which contains the entire ACT RTX hemolysin domain, induces by contrast a transient membrane permeabilization that is rapidly reverted in a time scale of minutes (≈30 min) by a repair pathway activated by extracellular Ca 2+ influx and that requires ATP [ 84 ] (Etxaniz et al, manuscript in revision). The increase of intracellular Ca 2+ induced by the sublytic doses of ACT was found to be very limited [ 84 ] (Etxaniz et al, manuscript in revision), and translocation of the adenylate cyclase domain into the cytosol of the macrophages consumes cellular ATP; both factors might contribute to the incapability of the ACT-treated cells to reseal the injured membrane [ 84 ] (Etxaniz et al, manuscript in revision).…”
Section: Act Toxin: An Adenylate Cyclase Enzyme Fused To An Rtx Hementioning
confidence: 99%
See 2 more Smart Citations
“…The “pore model” for AC translocation proposed here may thus explain why ACT is apparently weakly haemolytic relative to other RTX pore-forming toxins, such as Escherichia coli α-haemolysin, which do not possess an equivalent N-terminal domain [ 18 , 19 ]. Supporting this idea that in native conditions the presence of the AC domain somehow blocks the ion flux through the ACT pore, others previously observed that the elimination of the AC domain plus residues of the translocation region from the ACT polypeptide made the mutant toxins to exhibit a lytic potency comparable to the RTX toxins [ 52 , 53 ]. Future work will be needed to further prove this effect and map interactions between the AC domain and residues at the pore entrance.…”
Section: Discussionmentioning
confidence: 97%